Research on Mechanical Characteristics of High-Toughness Anti-Slip Pile Based on Slope Anti-Slip Stability Enhancement - Changzhu Xing; Yanwei Yang; Chuanfeng Zheng; Dayu Liu; Haigang Li; Liying Guo; Weitao Lin; Chengda Wang (Buildings)
Aiming at the problem of insufficient slope stability in deep foundation pit engineering, this paper takes the integrated urban and rural water supply project in Lingao County as the research object, simulates and analyzes the landslide process of the slope by using the strength discount method, and explores the mechanical response characteristics of the anti-slip piles in depth. It is found that the traditional anti-slip pile is prone to early failure due to bending and tensile damage in the middle of the pile back, which leads to the decline of slope stability. For this reason, this paper designs and studies the high-toughness anti-slip pile material and carries out numerical simulation analyses on C30 concrete anti-slip piles and high-toughness concrete anti-slip piles, respectively, for 9 working conditions, for a total of 18 working conditions. The results show that the bending and tensile toughness and strength of the anti-slip piles are significantly improved by using high-toughness material, which effectively avoids bending and tensile damage, and the slope safety coefficient is increased by 32.10%. Furthermore, the optimized design of anti-slip piles in terms of material, pile length, and pile position can effectively improve the stability of slopes and prolong the service life of the anti-slip piles, which provides a new way of thinking and methodology for the safety design of the deep foundation pit project. Thus, this study has important theoretical significance and engineering application value.